Prediction of the strength and timing of sunspot cycle 25 reveal decadal-scale space environmental conditions - Prantika Bhowmik (Nature Portfolio, 2018)
The Sun’s activity cycle impacts space-reliant technologies and the Earth’s climate, but predicting this is challenging. An ensemble forecast based on an innovative combination of two solar magnetic field evolution models indicates a weak, but not insignificant sunspot cycle 25 peaking in 2024.